Wortmannin Potentiates Integrase-Mediated Killing of Lymphocytes and Reduces the Efficiency of Stable Transduction by Retroviruses - Daniel, René (American Society for Microbiology, 2001)
Retroviral infection induces integrase-dependent apoptosis in DNA-PK-deficient murine scid lymphocytes. Furthermore, the efficiency of stable transduction of reporter genes is reduced in adherent cell lines that are deficient in cellular DNA-repair proteins known to mediate nonhomologous end joining (NHEJ), such as DNA-PK and XRCC4 (R. Daniel, R. A. Katz, and A. M. Skalka, Science 284:644–647, 1999). Here we report that wortmannin, an irreversible inhibitor of phosphatidylinositol 3-kinase (PI-3K)-related PKs, including the catalytic subunit of DNA-dependent protein kinase (DNA-PK(CS)) and ATM, sensitizes normal murine lymphocytes to retrovirus-mediated cell killing. We also show that the efficiency of stable transduction of reporter genes in human (HeLa) cells, mediated by either an avian sarcoma virus or a human immune deficiency virus type 1 vector, is reduced in the presence of wortmannin. The dose dependence of such reduction correlates with that for inhibition of PI-3K-related protein kinase activity in these cells. Results from wortmannin treatment of a panel of cell lines confirms that formation and/or survival of transductants is dependent on components of the NHEJ pathway. However, stable transduction is virtually abolished by wortmannin treatment of cells that lack ATM. These results suggest that ATM activity is required for the residual transduction observed in the NHEJ-deficient cells. Our studies support the hypothesis that DNA repair proteins of the NHEJ pathway and, in their absence, ATM are required to avoid integrase-mediated 2killing and allow stable retroviral DNA transduction. The studies also suggest that cells can be sensitized to such killing and stable retroviral DNA integration blocked by drugs that inhibit cellular DNA repair pathways.